PENGEMBANGAN KONSEP TOTAL QUALITY MANAGEMENT - Soemantri, Roebiandini (JURNAL ILMU MANAJEMEN DAN BISNIS, 2013)
This research was aimed to develop TQM concept for State Owner’s Financial Service Company Bandung City Branch by determining which elements stated important for developing TQM for State Owner’s Financial Service Company Bandung City Branch and this study was willing to know the adoption of those elements at State Owner’s Financial Service Company Bandung City Branch. Number of respondent companies involved in this study is 21 branch offices. The respondents who participate in this study are branch managers and head of department from each of branch office. The study was conducted to determine the perception of respondent managers and head of departments as to the critical strategy that should define a particular TQM. The validation TQM is done by conducting Factor Analysis. The result from the survey is that the original of 72 elements of TQM is remain 45 elements which are grouped into 6 (six) factors. Those factors are Education and Analysis Tools Supporting, Facility Management, Management Commitment and Quality Leadership, Customer Focus, Mesurement and Benchmarking.